Asymptotic analysis of space-time codes in non-gaussian noise and interference - Nezampour, Ali; Schober, Robert; Ma, Yao (IEEE Vehicular Technology Conference, 2008)
In this paper, we provide a framework for the asymptotic performance analysis of space-time codes (STCs) in correlated Ricean fading and non-Gaussian noise and interference. In particular, we derive a simple, asymptotically tight expression for the pairwise error probability (PEP) of coherent STCs which is valid for any type of noise and interference with finite moments. This PEP expression can be used to obtain accurate asymptotic approximations for the bit and symbol error probabilities of STCs. Our results show that while the diversity gain of an STC is independent of the type of noise, the coding gain is not and depends on certain moments of the noise and interference. We provide closed-form expressions for these moments for several practically relevant types of noise and interference. Our analytical findings are confirmed by simulations for Alamouti's ST block code and Tarokh's ST trellis code and several different types of noise and interference. © 2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03